Interspecies transmission of SARS-CoV-2 - Bailey, Dalan (Henry Stewart Talks, 2021)
Why viruses must mutate for interspecies transmission, Overview of SARS-CoV-2 infection of cells, Tropism of bat coronavirus RaTG13 and SARS-CoV-2, Studying the mutations allowing interspecies transmission of the virus, The main mutations found so far in SARS-CoV-2 allowing interspecies transmission to human, Possibilities of cross-species transmission from humans, More information about the study described by Dr Bailey can be found in the PLOS Biology article: ‘The SARS-CoV-2 Spike protein has a broad tropism for mammalian ACE2 proteins’ https://doi.org/10.1371/journal.pbio.3001016. Of note, the mutagenesis studies using RaTG13 and SARS-CoV-2 Spike described by Dr Bailey were performed using pseudotype systems and codon-optimised Spike expression constructs. These mutations were not built into replication competent viruses.